1993
DOI: 10.1111/j.1471-4159.1993.tb03585.x
|View full text |Cite
|
Sign up to set email alerts
|

Aurintricarboxylic Acid Prevents NMDA‐Mediated Excitotoxicity: Evidence for Its Action as an NMDA Receptor Antagonist

Abstract: The effect of the endonuclease inhibitor aurintricarboxylic acid (ATA) versus NMDA-mediated delayed cell death was examined in an ex vivo chick retinal preparation. Transient exposure to 100 microM NMDA for 60 min followed by a 24-h recovery period resulted in a sevenfold increase in lactate dehydrogenase (LDH) release into the medium. ATA at 100 microM significantly reduced NMDA-mediated LDH release by 60%. In clarifying the mechanism of protection versus NMDA, ATA was found to inhibit several acute NMDA-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…SD, n = 5 ) . These results suggest that kainate-induced plasma membrane damage is a consequence, rather than a cause, of DNA damage, but should be interpreted with caution, because the pharmacological actions of ATA are known not to be restricted to inhibition of endonucleases (Batistatou and Greene, 1991;Zeevalk et al, 1993;Yasuda et al, 1995).…”
Section: Kainate-induced Olc Plasma Membrane Damage Is Prevented By Tmentioning
confidence: 88%
“…SD, n = 5 ) . These results suggest that kainate-induced plasma membrane damage is a consequence, rather than a cause, of DNA damage, but should be interpreted with caution, because the pharmacological actions of ATA are known not to be restricted to inhibition of endonucleases (Batistatou and Greene, 1991;Zeevalk et al, 1993;Yasuda et al, 1995).…”
Section: Kainate-induced Olc Plasma Membrane Damage Is Prevented By Tmentioning
confidence: 88%
“…The ability of ATA to block glutamate or N-methyl-D-aspartate (NMDA) neurotoxicity has been confirmed on cultured hippocampal neurons (Samples and Dubinsky, 1993), hippocampal neurons in vivo (Roberts-Lewis et al, 1993), and chick retinal neurons (Zeevalk et al, 1993). However, Dessi et al (1993) found that neither ATA nor protein synthesis inhibitors protected cerebellar granule cells against glutamate neurotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…However, Dessi et al (1993) found that neither ATA nor protein synthesis inhibitors protected cerebellar granule cells against glutamate neurotoxicity . Of further interest was the observation of Zeevalk et al (1993) that ATA is a competitive NMDA antagonist, able to displace ['HICGS 19755 with an ICs0 of 27 pM.…”
Section: Introductionmentioning
confidence: 99%
“…After these observations, ATA was also demonstrated to act in an endonuclease-independent manner to interact with several cellular targets, which might also contribute to its antiapoptotic effects. These include the topoisomerases (Benchokroun et al, 1995), the interferon-␣ and N-methyl-D-aspartate receptors (Zeevald et al, 1993), and different important signaling cascades. For example, it is a potent activator of the mitogen-activated protein kinase (MAPK) cascade in PC-12 (Okada and Koizumi, 1995) and Nb2 lymphoma (Rui et al, 1998) cells.…”
mentioning
confidence: 99%